A Sociolinguistic Analysis of Language Style Differences between Male and Female Students in Whatsapp Group - Alya Rahmawati; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the language differences between women and men used in conversations or chats in the WhatsApp group of English Literature class B UIN Bandung. This research uses descriptive qualitative method with data obtained through copying and screenshots of several conversations from WhatsApp groups selectively, by keeping the identity of the message sender confidential. The data were analyzed based on differences in diction, language style, and ways of conveying information between male and female members. The results of the analysis show that men tend to use language that is more direct, concise, and to the point, while women are more expressive, polite, and use expressions that show emotion or social concern. The findings suggest that digital communication styles still reflect gendered communication patterns. This research is expected to contribute to sociolinguistic studies, especially in understanding the dynamics of language in digital media.